Swollen Disc in Children : Diagnostic Approach - Prihatningtias, Riski (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Swollen disc is a clinical sign of eye disease, neurological or systemic. It happened because of the increase in intracranial. Some of the conditions that cause swollen disc are optic neuritis, optic neuropathy, retinal vein occlusion, papilloedema, or pseudo-disc swelling (e.g drusen). In children, the incidence of swollen discs differs from that in adults. Diagnosis can be made using OCT (Optical Coherence Tomography), ocular ultrasound, VEP (Visual Evoked Potential) and MRI (Magnetic Resonance Imaging) of the orbit and head